You can count on this: barcoded hematopoietic stem cells - Glimm, Hanno; Ball, Claudia R.; Kalle, Christof von (Cell stem cell, 2011)
Understanding how individual hematopoietic stem cells contribute to blood formation requires analysis at the single-cell level. Recently in Nature Biotechnology, Lu et al. (2011) tagged HSCs with unique molecular barcodes and used high-throughput sequencing to track their progeny after transplantation.